Tindak Pidana Penipuan dalam Media Jual Beli Online - Pramesti, Yusri Ardiyah; Rosnawati, Emy (Indonesian Journal Publisher, 2023)
The formulation of this research is the regulation of criminal law for fraud in online buying and selling and forms of criminal liability for fraudulent acts of online buying and selling in Indonesia. This type of research is normative juridical. The approach of this research is the statute approach, and the conceptual approach. Research legal materials include primary, secondary, and non-legal materials. The analysis of legal materials uses a qualitative and comprehensive analysis. The results of the study state that 1) the regulation of criminal law in Indonesia, the crime of buying and selling fraud committed online is contained in Article 28 Paragraph (1) of the ITE Law, but this article is specifically used for online fraud crimes which have characteristics only in buying and selling activities. online, while Article 378 of the Criminal Code can only be used to take action against perpetrators of conventional fraud crimes, 2) a form of criminal responsibility for perpetrators of online buying and selling fraud, namely criminal sanctions based on Article 45 paragraph 2 of the ITE Law.